2001
DOI: 10.1083/jcb.200107075
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high curvature membranes mediated by direct endophilin bilayer interactions

Abstract: Endophilin 1 is a presynaptically enriched protein which binds the GTPase dynamin and the polyphosphoinositide phosphatase synptojanin. Perturbation of endophilin function in cell-free systems and in a living synapse has implicated endophilin in endocytic vesicle budding (Ringstad, N., H. Gad, P. Low, G. Di Paolo, L. Brodin, O. Shupliakov, and P. De Camilli. 1999. Neuron. 24:143–154; Schmidt, A., M. Wolde, C. Thiele, W. Fest, H. Kratzin, A.V. Podtelejnikov, W. Witke, W.B. Huttner, and H.D. Soling. 1999. Nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

32
581
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(616 citation statements)
references
References 17 publications
32
581
1
2
Order By: Relevance
“…Bif-1, also known as SH3GLB1 or Endophilin B1, was originally discovered as a Bax-binding protein 16,17 . Although Bif-1 has liposome tubulation activity in vitro, it appears as though this protein does not localize to transferrinpositive endosomes 18 . Recent studies have shown that Bif-1 associates with membranes of intracellular organelles, such as the Golgi apparatus 18, 19 and mitochondria 20, 21 , and has been implicated in vesicle formation and membrane dynamics.…”
mentioning
confidence: 95%
“…Bif-1, also known as SH3GLB1 or Endophilin B1, was originally discovered as a Bax-binding protein 16,17 . Although Bif-1 has liposome tubulation activity in vitro, it appears as though this protein does not localize to transferrinpositive endosomes 18 . Recent studies have shown that Bif-1 associates with membranes of intracellular organelles, such as the Golgi apparatus 18, 19 and mitochondria 20, 21 , and has been implicated in vesicle formation and membrane dynamics.…”
mentioning
confidence: 95%
“…These proteins, which interact with dynamin through its C-terminal pro/arg-rich domain (PRD), fall into several functionally distinct classes. They include actin-binding proteins, e.g., cortactin and mAbp1 Kessels et al, 2001); scaffolding molecules, e.g., intersectin, syndapin, grb2, and nck, which link dynamin to N-WASP and other proteins (Gout et al, 1993;Roos and Kelly, 1998;Peter et al, 2004;Schmitz et al, 2004); and membrane-active molecules, e.g., endophilin and amphiphysin, that can sense and/or generate membrane curvature (Schmidt et al, 1999;Farsad et al, 2001;Peter et al, 2004). In the case of actin dynamics, there is growing evidence that dynamin can regulate the activity of some of these accessory proteins (Schafer et al, 2002).…”
mentioning
confidence: 99%
“…In vivo, over-expression of the BAR domain of human Amphiphysin II in tissue culture cells causes invagination of the plasma membrane to form internal tubules that resemble the T-tubules of skeletal muscle involved in excitationcontraction coupling (6). As well as the BAR domain, the N-terminal region also plays an important role in membrane bending (7). This auxilliary region is likely to undergo a random coil to helical transition on engagement with the membrane (2).…”
mentioning
confidence: 99%